Viscosity, relaxation and fragility of the Ca65Mg15Zn20 bulk metallic glass. (June 2019) - Liu, B.B.; Hu, L.; Wang, Z.Y.; Ye, F.
Abstract: The fragility of Ca65 Mg15 Zn20 bulk metallic glass was evaluated from calorimetric kinetics by differential scanning calorimeter and viscosity measurement. From the thermal analysis, the glass transition width was carefully determined to estimate the fragility, and the obtained fragility parameter D ∗ is dependent on the pre-factor while the fragility index m keeps invariable, which indicates that m will be more reliable to display the fragility behavior. The viscosity in both the melt state and supercooled liquid region was measured and fitted using different equations as well. The fragility index m estimated from calorimetric method is smaller than that from viscosity in the supercooled liquid region which is ascribed to that the calorimetric evaluation of fragility corresponds to the glass state (non-equilibrium state) rather than supercooled liquid state (equilibrium state). The measured viscosity in the melt state is smaller than that predicted by VFT and Mauro equation when extrapolating the value from the supercooled liquid region to higher temperatures. This deviation implies that different regimes of dynamic behavior exists in the two states, and a dynamic crossover of viscosity may occur at the critical temperature T c as suggested by the mode coupling theory. Highlights: The fragility was evaluated from both calorimetric kinetics and viscosity measurement. The fragility index m is more reliable than fragility parameter D * to display the fragility behavior. The fragility index m obtained from DSC is lower than that from viscosity in the SCL region. A dynamic crossover of viscosity lies in the glass formation upon cooling.